2010
DOI: 10.3855/jidc.540
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility patterns of community-acquired uropathogens in Tehran, Iran

Abstract: Background: Antibiotic resistance of urinary tract pathogens has increased worldwide. Knowledge of the antibiotic resistance patterns of uropathogens in specific geographical locations is an important factor for choosing an appropriate empirical antimicrobial treatment. The aim of this study was to provide information regarding local resistance patterns of urinary pathogens to the commonly used antibiotics in Tehran, Iran. Methodology: Urine samples collected and submitted to two pathobiology laboratories in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
92
7
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 18 publications
28
92
7
3
Order By: Relevance
“…Discoveries indicated that lineages of E-coli are sensitive to this antibiotic respectively 66% and 2.62%. These results were the same as other Iranians researches (11). This findings showed that using Fluoroquinolones in treatments should seriously be controled and an efficient strategy to counter and stop the increased resistance of this antibiotic should be considered.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Discoveries indicated that lineages of E-coli are sensitive to this antibiotic respectively 66% and 2.62%. These results were the same as other Iranians researches (11). This findings showed that using Fluoroquinolones in treatments should seriously be controled and an efficient strategy to counter and stop the increased resistance of this antibiotic should be considered.…”
Section: Discussionsupporting
confidence: 75%
“…Urinary tract infection is one of the most common medical problems in females and also in this study a large portion of patients consisted of females (36.84%). This number is very close to pathfinder's and his/her colleagues (11) and Rostam zade khamene (12) results. As we expected based on previous studies (13,14) Escherichia coli has the highest frequency among pathogens (57.64%).…”
Section: Discussionsupporting
confidence: 67%
“…Our study also showed the similar fi ndings with 28.5-30.35% resistance to quinolones, 39.2-50.0% resistance to cephalosporins and 48.21% resistance to cotrimoxazole for gram negative isolates 17 . The results showed a considerable increase in resistivity of gram negative isolates to amoxycillin (80.36%) which was supported by several studies 11,12,18 . Nitrofurantoin demonstrated better activity against gram negative (98.21% susceptible) as well as gram positive isolates (100.0% susceptible), in agreement with data published by others 17,18,19 .…”
Section: Discussionsupporting
confidence: 71%
“…The results showed a considerable increase in resistivity of gram negative isolates to amoxycillin (80.36%) which was supported by several studies 11,12,18 . Nitrofurantoin demonstrated better activity against gram negative (98.21% susceptible) as well as gram positive isolates (100.0% susceptible), in agreement with data published by others 17,18,19 . The high level susceptibility of uropathogens to nitrofurantoin may be the narrow spectrum of activity, narrow tissue distribution (low or undetectable serum concentration) and limited contact with bacteria outside the urinary tract 20 .…”
Section: Discussionsupporting
confidence: 71%
“…Urinary tract infection (UTI) is one of the common infections in pediatric wards, worldwide (1,2). Urinary tract infection can be nosocomial or community acquired (3). It is defined as the growth of > 10 5 CFU/mL of a single pathogen from properly collected urine specimen of children with febrile disease or UTI symptoms (4).…”
Section: Introductionmentioning
confidence: 99%